The Effect of Psychodrama on the Level of Assertiveness in Neglected and Abused Adolescents. - ŞİMŞEK, Çağlar; YILDIRIM, Ejder Akgün; KAYIR, Arşalus (Fenerbahce University Journal of Health Sciences (FBU-JOSH) / Fenerbahçe Üniversitesi Sağlık Bilimleri Dergisi, 2024)
This study aims to examine the effect of psychodrama on the level of assertiveness in neglected and abused adolescents. After obtaining the institutional permission for this study, T.C. ethics committee approval was obtained from the Ministry of Health Provincial Health Directorate X Training and Research Hospital Clinical Research Ethics Committee The population of the study consisted of 21 adolescents and the sample consisted of 13 volunteer adolescents between the ages of 14-18, determined by purposeful sampling technique. The study was conducted between March- May 2017 in child support centers. Psychodrama sessions lasted twice a week for 9 weeks, each session for 3 hours; a total of 18 sessions of psychodrama were conducted. Measurements were carried out before and after psychodrama practice as pre and post-tests. Rathus Assertiveness Schedule (RAS) was used as a data collection tool. The data were analyzed using the SPSS (Statistical Package for the Social Sciences) 18.0 package program. Continuous variables are given as mean ± standard deviation and categorical variables as numbers and percentages. In dependent group comparisons, when the parametric test assumptions were provided, the significance test of the difference between the two partners was used; If the parametric test assumptions were not provided, the Wilcoxon Paired TwoSample Test was used. After psychodrama, the assertiveness scores of adolescents increased compared to before psychodrama. Psychodrama is an effective method to increase the assertiveness levels of adolescents.